Revamping a former landfill into an energy park in Alam Impian, Shah Alam - Ab Maalek, Nur Tihani; Abu Bakar, Aniza; Ibrahim, Putri Haryati; Yaman, Maheran (IIUM Press, 2024)
This project takes place in a former landfill in Alam Impian, Shah Alam, where it aims to repurpose a former landfill into a community-friendly energy park by addressing social, environmental and economic aspects. The energy park aims to educate the users on energy and waste management, the process of waste from site for environmental care, and the creation of opportunities for nearby sites to be developed into more commercialised land use and systems that help the site to be self-sustained. Document analysis, site inventory and SWOT analysis were carried out along with risk assessments to identify the site's potential and constraints. The analysis was concluded with an Analysis of Interconnected Decision Areas (AIDA) for synthesis. In order to achieve the aim of this project, Waste-to-Energy was developed as the design concept to tackle the available resources into electric energy and user-friendly energy park.